Fundamentals of risk and insurance - Vaughan, Emmett J.; Vaughan, Therese M. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
"Fundamentals of Risk and Insurance, 11th Edition presents a thorough and comprehensive introduction to the field of insurance while emphasizing the consumer. The new edition first examines the concept of risk, the nature of the insurance device, and the rinciples of risk management. It then discusses the traditional fields of life and health insurance as solutions to the risks connected with the loss of income. Fundamentals of Risk and Insurance, 11th Edition alsodeals with the risks associated with the ownership of property and legal liability. "--
Machine generated contents note: Chapter 1: The Problem of Risk Chapter 2: Introduction to Risk Management Chapter 3: The Insurance Device Chapter 4: Risk Management Applications Chapter 5: The Private Insurance Industry Chapter 6: Regulation of the Insurance Industry Chapter 7: Functions of Insurers Chapter 8: Financial Aspects of Insurer Operations Chapter 9: The Legal Framework Chapter 10: Managing Personal Risks Chapter 11: Social Insurance Programs Chapter 12: Introduction to Life Insurance Chapter 13: The Actuarial Basis of Life Insurance Chapter 14: The Life Insurance Contract--General Provisions Chapter 15: The Life Insurance Contract--Other Provisions Chapter 16: Special Life Insurance Forms Chapter 17: Buying Life Insurance Chapter 18: Annuities and Pension Benefits Chapter 19: Managing the Retirement Risk Chapter 20: Health Insurance: Disability Income Insurance Chapter 21: Health Insurance: Coverage for Medical Expenses Chapter 22: Health Insurance for the Elderly Chapter 23: Employee Benefits and Other Business Uses of Life and Health Insurance Chapter 24: The Homeowners Policy--General Provisions Chapter 25: The Homeowners Policy Forms Chapter 26: Other Personal Forms of Property Insurance Chapter 27: Negligence and Legal Liability Chapter 28: General Liability Insurance for the Individual Chapter 29: The Automobile and its Legal Environment Chapter 30: The Personal Auto Policy Chapter 31: Commercial Property Insurance Chapter 32: Commercial Liability Insurance Chapter 33: Surety Bonds and Trade Credit Insurance Chapter 34: Insurance in the Future .
Includes bibliographical references and index.
Keywords: Insurance; Risk (Insurance); BUSINESS & ECONOMICS / Insurance / Risk Assessment & Management